2017
DOI: 10.1016/j.jascer.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Defects and microstructure of a hydrothermally derived (Bi1/2K1/2)TiO3powder

Abstract: Fine powders of bismuth potassium titanate (Bi 1/2 K 1/2)TiO 3 (BKT) synthesized by hydrothermal reactions have been reported to have good sinterability and high chemical stability against long-time sintering. In this study, detailed chemical and structural characterizations were performed on a hydrothermal BKT powder sample to identify the origin of such properties. The results of X-ray diffraction, infrared transmittance, and diffuse reflectance measurements revealed that the hydrothermal BKT particle contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This greater tetragonal distortion of the BKZT powders is attributed to their large concentration of lattice hydroxyl groups, which are believed to align along the c axis. 22) The crystal structure after these hydroxyl groups were eliminated by a heat treatment are presented later in this paper. In contrast to the patterns of samples with low Zr contents, the patterns of the sample with x = 0.15 shows additional peaks from Bi 2 O 3 and ZrO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This greater tetragonal distortion of the BKZT powders is attributed to their large concentration of lattice hydroxyl groups, which are believed to align along the c axis. 22) The crystal structure after these hydroxyl groups were eliminated by a heat treatment are presented later in this paper. In contrast to the patterns of samples with low Zr contents, the patterns of the sample with x = 0.15 shows additional peaks from Bi 2 O 3 and ZrO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…22) Thus, to investigate the impact of a heat treatment on the phase purity and the crystal structure of the BKZT powders synthesized from (Zr x Ti 1¹x )O 2 · nH 2 O (0.00¯x¯0.10), samples were heated at 1000°C for 1 h. No significant change in the particle size and morphology was observed for all of the samples after the heat treatment. The XRD profiles of the heat-treated BKZT powders are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted detailed structural characterizations on the hydrothermal BKT powder to understand the origin of its excellent sinterability. 26) The transmission electron microscopy (TEM) observation [Fig. 3(a)] in combination with an elemental analysis revealed that the surface of the hydrothermally synthesized BKT particles is covered with a large number of nanoparticles of Bi 2 O 3 .…”
Section: Processingmentioning
confidence: 99%
“…Bi 4 Ti 3 O 12 and K 2 Ti 6 O 13 , were observed in this sample (the details of which are shown in the supplementary information). Moreover, the volatilization of Bi 2 O 3 and K 2 CO 3 at high temperature hinders the highly dense pure BKT ceramics, which results in low electrical properties and poor understanding of its basic properties [20,21]. The piezoelectric properties of the pure BKT ceramic are not generally high enough for most applications.…”
Section: Introductionmentioning
confidence: 99%